Pengaruh Kualitas Pelayanan Administrasi dan Citra Sekolah Terhadap Kepuasan Siswa di SMK YPI Darussalam 2 Cerme Gresik - Tasya Nabila Nur Azmi; Durinta Puspasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of service quality and school image on student satisfaction. This research uses a quantitative approach with an explanatory research design. The population consists of 270 students of grade X and XI at SMK YPI Darussalam 2 Cerme Gresik, with a sample of 159 respondents obtained through a Sample Size Calculator and proportional stratified random sampling technique. Data were collected using a closed-ended questionnaire with a 5-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 27. The results show that partially, the service quality variable has a t-value of 6.165 with a significance of 0.000 < 0.05, indicating a positive and significant effect on student satisfaction. The school image variable has a t-value of 4.043 with a significance of 0.000 < 0.05, indicating a positive and significant effect on student satisfaction. Simultaneously, both variables have a significant effect with an F-value of 132.768 and a significance of 0.000 < 0.05. The coefficient of determination (R²) of 0.630 indicates that 63.0% of the variation in student satisfaction can be explained by service quality and school image, while the remaining 37.0% is influenced by other variables outside this study. Thus, service quality and school image have a substantial contribution to student satisfaction, with service quality being the more dominant factor in influencing student satisfaction.